A Bibliometric Analysis of Digital Transformation in Local Governments: Trends, Themes, and SDG Perspectives (2015–2025) - Muhammad Kholis; Achmad Nurmandi; Herman Lawelai; Muhammad Younus; Wahdania Suardi (FAKULTAS DAKWAH UIN SALATIGA, 2026)
Digital transformation at the subnational level is essential for improving public services and supporting SDGs. Yet it still faces constraints, including infrastructure gaps, limited digital capacity, and weak intergovernmental coordination. This study conducts a bibliometric analysis of 106 Scopus-indexed articles published between 2015 and 2025 using PRISMA and Bibliometrix (RStudio) to map research development, citation trends, and major thematic clusters. Results show a 39.55% annual growth rate, involvement of 420 authors, 62 publication sources, and 20.75% international collaboration. The dominant keyword clusters include digital transformation, local government, e-government, digital readiness, and SDGs. Although global research increasingly links digitalization with sustainability goals, policy fragmentation and unequal technological preparedness remain significant barriers. The study emphasizes the need for coordinated, capacity-building, and inclusive digital governance strategies to strengthen the impact of digital transformation on regional sustainable development.